Desain Analisis Etika dan Literasi Data dalam Pendidikan Dasar: Studi Eksploratif pada Pembelajaran Matematika Berbasis Big Data - Radira Ayu Faniya Putri; Afida Rahma Tsabita (Education : Jurnal Sosial Humaniora dan Pendidikan, 2024)
The rapid growth of big data and digital platforms has transformed the educational landscape, including primary education, where students actively engage with data through various learning technologies. However, the integration of data literacy and digital ethics into classroom instruction remains underdeveloped, especially in subjects like mathematics. This exploratory study aims to examine how mathematical learning at the elementary level can be utilized to introduce critical awareness of data and ethical use of digital tools. Using a qualitative case study approach, the research involved classroom observations, interviews with teachers and students, and the development of a pedagogical model integrating ethical and data literacy components. The findings reveal that while students interact with data daily, their understanding of concepts such as data privacy and ethical information sharing is limited. Teachers acknowledge the importance of digital ethics but often lack concrete strategies for implementation. The study contributes a practical model for embedding data ethics into math instruction and highlights the need for curricular reform and teacher training to foster responsible digital citizenship from an early age.